University Students and ICT after the COVID-19 Crisis: Towards instrumental use and disconnection - Casas-Mas, Belén; Homont, Louis Pierre Philippe; Valecillos Vázquez, Carmen (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The article analyzes the use that UCM students make of ICT, after two years of the COVID-19 pandemic. It is found that women, more than men, stop doing things to navigate. The youngest university students are the ones who connect the most, sleep less because they are connected and connect to their social networks during classes. The daily management and maintenance of their social networks is not a burden. For personal relationships, men and women prefer face-to-face and binary people indistinctly. The upward trend in digital disconnection continues.